2017
DOI: 10.1080/19404476.2017.1300854
|View full text |Cite
|
Sign up to set email alerts
|

Curricular Factors in Middle School Teachers’ Motivation to Become and Remain Effective

Abstract: Research in education and psychology contributes to an understanding of how educators create contexts for learning that encourage intrinsic motivation and increase academic achievement. In this article, the researcher investigated how middle level teachers define effectiveness and identified what factors influence their motivation, both positively and negatively. The purpose of this study was to explore what factors teachers selfidentified as both supporting and hindering their professional motivation. An unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Initially, a general coding framework was created, which was based on a breadth of theoretical literature on how teachers create conditions for student engagement (e.g. Daniels 2016Daniels , 2017Dewey 1916Dewey /1997Dewey , 1938Dewey /2015George and Richardson 2019;Kelly et al 2014;Kumpulainen and Renshaw 2007;Marton and Tsui 2004;Mercer and Littleton 2007;Reeve 2013;Deci 2000, 2017;Turner et al 2014). The data were organised into primary as well as secondary data (see Table 2), which were cross-referenced with the primary data to identify more latent content (Graneheim, Lindgren, and Lundman 2017).…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Initially, a general coding framework was created, which was based on a breadth of theoretical literature on how teachers create conditions for student engagement (e.g. Daniels 2016Daniels , 2017Dewey 1916Dewey /1997Dewey , 1938Dewey /2015George and Richardson 2019;Kelly et al 2014;Kumpulainen and Renshaw 2007;Marton and Tsui 2004;Mercer and Littleton 2007;Reeve 2013;Deci 2000, 2017;Turner et al 2014). The data were organised into primary as well as secondary data (see Table 2), which were cross-referenced with the primary data to identify more latent content (Graneheim, Lindgren, and Lundman 2017).…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Based on the result of the interview, it was not just the effort from the principal to create a positive work atmosphere, but teachers should also could contribute with their own ways in shaping a supportive teaching environment. A study from Daniels (2017) towards teaching administrators related to this case also suggested that whenever teachers were able to create and had full control over how they design and run the class through technology-based instruction, not only teachers were motivated but also the students would be more academically successful. It was also suggested that in an uncontrolled context of teaching, teachers are suggested to find out and control the situation, especially in overcoming stress in term of ICT integration in teaching and learning process (Panisoara, et al, 2020).…”
Section: A Work Atmospherementioning
confidence: 97%
“…Because the better the working atmosphere, the more motivated the educators are in carrying out their obligations, such as utilizing digital technology, one of them. A motivating and supporting institutional environment could be achieved by making time for teachers to engage in a more complex conversation in which they encounter the problems (Daniels, 2017). The principal and teachers at SMAN 5 Takengon have been able to create a comfortable working atmosphere at school so that teachers are more motivated to learn to use digital technology.…”
Section: A Work Atmospherementioning
confidence: 99%
“…Several studies have been conducted to investigate teachers' motivation for participating in TPD activities. Daniels (2017) found that EFL teachers are motivated by the following factors: improving their competence in terms of effective teaching, feelings of autonomy, or by their administrators, TPD providers, or teacher trainers. In the Chinese educational context, Zhang et al (2021) indicated that several factors at the teacher level affect teachers' motivation for participating in TPD.…”
Section: Introductionmentioning
confidence: 99%